Learning from Ninjas: young people's films as a lens for an expanded view of literacy and language. Issue 6 (2nd November 2019) - Escott, Hugh; Pahl, Kate
ABSTRACT: This article examines young people's films to provide insights about language and literacy practices. It offers a heuristic for thinking about how to approach data that is collectively produced. It tries to make sense of new ways of knowing that locate the research in the field rather than in the academic domain. The authors develop a lens for looking at films made by young people that acknowledge multiple modes and materiality within their meaning-making practices. We make an argument about the cultural politics of research, to consider how the language and literacy practices of young people are positioned. We argue for more consideration of how language and literacy appear entangled within objects and other stuff within young people's media productions, so as to trouble disciplinary boundaries within and beyond literacy and language studies.